Strategi Kepala Sekolah Dalam Penguatan Pendidikan Karakter Melalui Gerakan Literasi Sekolah - Riyanti, Sri; Ahmad, Syarwani; Harris, Helmi (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2021)
This study aims to determine the principal's strategy in strengthening character education through the School Literacy Movement at SDN 187 Palembang. This study uses a descriptive method with a qualitative approach. There are six informants in this study. The data collection techniques used were documentation, interviews, and observations. The data analysis technique used is data reduction, data presentation, and drawing conclusions and then testing the validity of the data. Based on the results of data analysis that has been done previously, it can be concluded that there is a strategy carried out by the principal of SDN 187 Palembang in strengthening character education in students through the School Literacy Movement (GLS) which consists of implementing policies for the School Literacy Movement activities and implementing strategies for attracting reading interest from students is done by giving rewards to students, reading books 10-15 minutes before learning, book corners and increasing the convenience of the library.